A new large‐scale and cost‐effective restoration method for cold‐water coral gardens. Issue 5 (17th March 2020) - Montseny, Maria; Linares, Cristina; Viladrich, Núria; Capdevila, Pol; Ambroso, Stefano; Díaz, David; Gili, Josep‐Maria; Gori, Andrea
Abstract: Gorgonians dwelling on the Mediterranean continental shelf are among the most frequent fishing bycatch taxa. These species display several traits, such as long lifespans and slow growth, which make them very vulnerable to the impacts caused by fishing activities with far‐reaching and long‐lasting effects. Hence, restoration and mitigation actions are crucial to enhance and speed up the natural recovery of damaged cold‐water coral gardens. Given the growing concern to develop effective and affordable restoration actions, the present study aims to propose and technically validate a new large‐scale and cost‐effective restoration method. This technique, named 'badminton method', consists of attaching bycatch Eunicella cavolini colonies to cobble supports and returning them to the continental shelf by gently throwing the gorgonian transplants directly from a boat. Two consecutive field experiments were conducted in order to find the best cobble type support and gorgonian size to be used: first, to evaluate the landing efficiency of gorgonian transplants at different depths (from 5 to 30 m) and second, to evaluate their capability to maintain a correct position over time. Natural cobbles with large gorgonians attached were the best option. Field results and modelling approaches suggest that the transplants would correctly land on the continental shelf seabed in a predicted area of around 60 m 2 . Moreover, they would successfully maintain an upright position ensuring gorgonian survival over time. The success of this method highlights the feasibility of large‐scale and low‐cost restoration actions with promising results for the conservation and recovery of cold‐water coral gardens.